KULIAH KERJA NYATA UNIMAR 2025: IMPLEMENTASI PENGABDIAN MASYARAKAT BERDAMPAK DI KECAMATAN CISOKA, KABUPATEN TANGERANG - Anni Rohimah; La Ode Akbar Rasydy; Abu Naim; Yogi Gumilar; Rosidawaty Rosidawaty; Dindin Aminudin; Nurul Setiani; Jaka Supriyanta; Abdul Aziz Setiawan; Dadang Dadang; Fitria Budi Utami; Sena Atmaja (Jurnal Abdi Insani, 2026)
Fiels Study and Community Service Program is the realization of community service by Unimar students and lecturers in rural community development. Unimar's 2025 Fiels Study and Community Service Program was conducted in four villages in Cisoka District, namely Jeungjing, Cisoka, Caringin, and Bojong Loa. The scope of activities carried out included education, health, social, and religious fields. The objective of Unimar's Fiels Study and Community Service Program activities is to train students' soft skills so they can have a positive impact on the community. The activity was opened by the Regent of Tangerang and the release was carried out by the Cisoka Subdistrict Head. The method used was participatory, involving the community. The programs carried out included education, social, health, MSME empowerment, and simple technological innovations. The output of Fiels Study and Community Service Program was to show an increase in community participation in maintaining environmental health, awareness of stunting prevention, and strengthening collaboration between students and villagers. The Fiels Study and Community Service Program program is a tangible manifestation of campus-community synergy in achieving Sustainable Development Goals (SDGs) 3 (Good Health and Well-being) and 6 (Clean Water and Sanitation). The outcomes of the service program include the availability of supporting facilities for waste management and sanitation.